Ketersediaan Ruang Terbuka Hijau di Lingkungan Permukiman Kebun Sari Ampenan Kota Mataram - Hartawan, Teddy (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Green Open Space (RTH) is an important element in urban spatial planning that functions to maintain the ecological, social, and aesthetic balance of an area, namely in the Kebun Sari Settlement Environment, Mataram City. The existence of Green Open Space located around the Jangkok River, precisely in the Settlement, is a public facility that is used by residents as a gathering place and provides great benefits, to maintain air circulation, absorb pollutants, and become a recreational space for the community. Mataram City, is a relevant case study to assess the availability of Green Open Space based on the standards set by SNI 2004. This study aims to analyze the existing condition of Green Open Space in Kebun Sari Village, identify its shortcomings, and provide recommendations for its development. With a qualitative descriptive method, we look at the condition of the object and study the analysis of the condition, impact and management of Green Open Space facilities in the Kebun Sari Ampenan Settlement. The current condition of green open space regarding the condition as in the comfort aspect itself can be functioned well, only the availability of Green Open Space in Kebun Sari Village has not met the standards set in PERMEN PU Number 5/PRT/M/2008. With the current area of ​​Green Open Space, the ecological, social, and aesthetic needs of the community have not been optimally met.